2023
DOI: 10.1007/s41685-023-00302-w
|View full text |Cite
|
Sign up to set email alerts
|

Pathways influencing bearers and abandoned farmlands through farmland intermediate management institutions: using prefectural data in Japan

Abstract: This study aimed to clarify relationships between regional factors and farmland utilization in the context of the current declining and aging population of Japan. We applied path analysis using prefectural data from the Ministry of Agriculture, Forestry, and Fisheries to investigate the effective ways of farmland use through farmland utilization programs such as the Farmland Intermediary Management Program as mediating influences based on prefectural regional characteristics. The main findings were as follows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For example, Hu et al (2023) and found that land transfer can significantly inhibit agricultural carbon emissions [5,21]. Gao et al (2023) analyzed the data of 46 prefectures in Japan based on a structural equation model and found that land transfer could effectively improve the efficiency of land resource allocation, inhibit land abandonment, and contribute to sustainable land development [22]. In fact, land transfer is not only a focal point in agricultural green transformation but also a key driver for agricultural technology progress [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hu et al (2023) and found that land transfer can significantly inhibit agricultural carbon emissions [5,21]. Gao et al (2023) analyzed the data of 46 prefectures in Japan based on a structural equation model and found that land transfer could effectively improve the efficiency of land resource allocation, inhibit land abandonment, and contribute to sustainable land development [22]. In fact, land transfer is not only a focal point in agricultural green transformation but also a key driver for agricultural technology progress [23].…”
Section: Introductionmentioning
confidence: 99%